Bureaucratic Reform and the Enhancement of Civil Service Performance : A Literature Review on the Merit System Policy in Indonesia - Karningsih Karningsih; Ari Satrio Wibowo (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This article examines the dynamics, challenges, and opportunities in implementing the merit system policy within the context of Indonesia’s bureaucratic reform, employing a narrative literature review approach using a triangulation of scholarly sources. Thematic analysis identifies five critical themes that hinder the implementation of the merit system: structural tensions between political patronage and meritocracy that create a hybrid spoils–merit system; significant institutional capacity gaps between central and local governments; digital transformation through platforms such as CAT, SmartASN, and SIPINTER as catalysts for transparency and objectivity; organizational cultural resistance rooted in patrimonial and seniority values; and the weakening of independent oversight exacerbated by the dissolution of KASN’s mandate. Although a progressive regulatory framework has been established through Law No. 5 of 2014, the implementation of the merit system remains constrained by persistent clientelism, limited institutional capacity, and cultural resistance. This study contributes to the theoretical discourse on Weberian bureaucracy, New Public Management, and good governance by confirming that the implementation of the merit system in developing countries constitutes a political–cultural transformation that requires fundamental changes in political incentive structures, institutional capacity, and organisational values. Managerial implications include strengthening independent oversight, making substantial investments in institutional capacity, accelerating inclusive digital transformation, and implementing systematic change management programs to expedite the transition toward a performance-based bureaucracy that is professional and integrity-driven in support of Indonesia’s Golden Vision 2045